2004
DOI: 10.1037/0021-843x.113.1.72
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Item Response Theory Analysis to Alcohol, Cannabis, and Cocaine Criteria in DSM-IV.

Abstract: Item response theory (IRT) is supplanting classical test theory as the basis for measures development. This study demonstrated the utility of IRT for evaluating DSM-IV diagnostic criteria. Data on alcohol, cannabis, and cocaine symptoms from 372 adult clinical participants interviewed with the Composite International Diagnostic Interview--Expanded Substance Abuse Module (CIDI-SAM) were analyzed with Mplus (B. Muthen & L. Muthen, 1998) and MULTILOG (D. Thissen, 1991) software. Tolerance and legal problems crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
236
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(292 citation statements)
references
References 25 publications
51
236
2
2
Order By: Relevance
“…Neglect of roles, activities given up, and legal problems were among the most severe criteria, a result consistent with previous studies whether conducted at the item (Kahler and Strong, 2006) or criterion (Langenbucher et al 2004;Proudfoot et al 2006;) level. Psychological/physical problems, social/interpersonal problems, and time spent criteria were also in the severe range of the observed continuum in this study, consistent with items tapping similar constructs in the studies by Krueger et al (2004) and Kahler and Strong (2006), but at variance with findings reported by Langenbucher et al (2004) that showed psychological/physical problems to be the least severe criterion, with the remaining criteria overlapping in the middle range of the observed severity continuum. Similar to prior research in this area, the quit/control, larger/longer, and hazardous use criteria were among the least severe (Krueger et al 2004;Kahler and Strong, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Neglect of roles, activities given up, and legal problems were among the most severe criteria, a result consistent with previous studies whether conducted at the item (Kahler and Strong, 2006) or criterion (Langenbucher et al 2004;Proudfoot et al 2006;) level. Psychological/physical problems, social/interpersonal problems, and time spent criteria were also in the severe range of the observed continuum in this study, consistent with items tapping similar constructs in the studies by Krueger et al (2004) and Kahler and Strong (2006), but at variance with findings reported by Langenbucher et al (2004) that showed psychological/physical problems to be the least severe criterion, with the remaining criteria overlapping in the middle range of the observed severity continuum. Similar to prior research in this area, the quit/control, larger/longer, and hazardous use criteria were among the least severe (Krueger et al 2004;Kahler and Strong, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Also consistent with prior research (Krueger et al 2004;Langenbucher et al 2004;Proudfoot et al 2006;Kahler and Strong, 2006;Saha et al 2006), the larger/longer dependence criterion was shown to have excellent discrimination and low severity. Taken together, these results suggest that the larger/longer criterion may represent a high-risk drinking pattern that serves as a bridging criterion linking the less severe end of the alcohol use disorder continuum with the more severe end.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Three of the abuse symptoms (hazardous use, interference with work or home, and social problems) appeared to be effective in making discriminations among the mild to moderate range of alcohol problem severity in this sample. However, as has been shown in other item response analyses of DSM-IV AUD criteria (Kahler and Strong, 2006;Krueger et al, 2004;Langenbucher et al, 2004;Proudfoot et al, 2006), abuse symptoms were not consistently less severe than dependence symptoms. Among the dependence symptoms, the larger/longer criterion appeared to be a particularly effective item for discriminating between those with heavy drinking and no AUD symptoms and those with at least some AUD symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, they have produced inconsistent results, with some studies supporting the coherence of dependence (Hasin et al 1988;Morgenstern et al 1994 ;Feingold & Rounsaville, 1995 ;Nelson et al 1999 ;Swift et al 2001;Langenbucher et al 2004) while others have identified multiple factors underlying dependence criteria (e.g. Kosten et al 1987).…”
Section: Introductionmentioning
confidence: 99%